Rok 2020 i inne opowiadania - Bizukojć, Maciej; Pruszyńska, Aleksandra; Kłudka, Mateusz; Czyż, Nikodem; Czekajło, Emilia; Siwicka, Anastazja; Szołtek, Mikołaj; Zawali, Dawid; Waga, Franciszek; Zotov, Yevhenii; Bogucka, Gabriela; Kravchenko, Tanya; et al. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
"The Year 2020 and Other Stories" is a collection of literary texts created by first-year students of journalism and social communication. The collection shows how the global crisis affected individual lives - emotionally, socially, and existentially - and how words can become a way of making sense of the unknown. It is a moving voice of a generation coming of age during the pandemic.
Keywords: nadzieja; miłość; przyjaźń; solidarność; strach; wirus; życie; hope; love; friendship; solidarity; fear; virus; life